Electrophysiological evidence of the time course of attentional bias in non-patients reporting symptoms of depression with and without co-occurring anxiety - Sass, Sarah M.; Heller, Wendy; Fisher, Joscelyn E.; Silton, Rebecca L.; Stewart, Jennifer L.; Crocker, Laura D.; Edgar, J. Christopher; Mimnaugh, Katherine J.; Miller, Gregory A. (Frontiers in Psychology, 2014)
Anxiety is characterized by attentional biases to threat, but findings are inconsistent for depression. To address this inconsistency, the present study systematically assessed the role of co-occurring anxiety in attentional bias in depression. In addition, the role of emotional valence, arousal, and gender was explored. Ninety-two non-patients completed the Penn State Worry Questionnaire (Meyer et al., 1990; Molina and Borkovec, 1994) and portions of the Mood and Anxiety Symptom Questionnaire (Watson et al., 1995a,1995b). Individuals reporting high levels of depression and low levels of anxiety (depression only), high levels of depression and anxiety (combined), or low levels of both (control) completed an emotion-word Stroop task during event-related brain potential recording. Pleasant and unpleasant words were matched on emotional arousal level. An attentional bias was not evident in the depression-only group. Women in the combined group had larger N200 amplitude for pleasant than unpleasant stimuli, and the combined group as a whole had larger right-lateralized P300 amplitude for pleasant than unpleasant stimuli, consistent with an early and later attentional bias that is specific to unpleasant valence in the combined group. Men in the control group had larger N200 amplitude for pleasant than unpleasant stimuli, consistent with an early attentional bias that is specific to pleasant valence. The present study indicates that the nature and time course of attention prompted by emotional valence and not arousal differentiates depression with and without anxiety, with some evidence of gender moderating early effects. Overall, results suggest that co-occurring anxiety is more important than previously acknowledged in demonstrating evidence of attentional biases in depression.